Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1139/o85-058
|View full text |Cite
|
Sign up to set email alerts
|

Actin and tubulin in Tetrahymena

Abstract: Tubulin and actin are cytoskeletal proteins known to play a major role in dividing cells. Tetrahymena pyriformis, a ciliated protozoan, was used as a model system for investigating tubulin synthesis during cilia regeneration and during the cell cycle. Until recently the identification of actin in Tetrahymena has been controversial. In this report evidence for the presence of actin in Tetrahymena is reviewed and control of actin gene expression during the cell cycle is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Maximum expression of THD2 occurred at 80 and 200 min, which were the times when the greatest numbers of cells were in micronuclear mitosis. The expression of ACT1, which does not change throughout the cell cycle, was monitored as a control (34,62). Since micronuclear DNA synthesis occurs immediately following anaphase, the observed peak of THD2 expression coincident with anaphase was consistent with the possibility that Thd2a might deacetylate newly deposited histones.…”
Section: Resultsmentioning
confidence: 94%
“…Maximum expression of THD2 occurred at 80 and 200 min, which were the times when the greatest numbers of cells were in micronuclear mitosis. The expression of ACT1, which does not change throughout the cell cycle, was monitored as a control (34,62). Since micronuclear DNA synthesis occurs immediately following anaphase, the observed peak of THD2 expression coincident with anaphase was consistent with the possibility that Thd2a might deacetylate newly deposited histones.…”
Section: Resultsmentioning
confidence: 94%
“…The (30) reported that a 47.5-kDa protein, which they considered to be actin, was partially purified from Tetrahymena cells by using a DNase I affinity column. Our results indicate that Tetrahymena actin does not inhibit DNase I activity at all.…”
Section: Resultsmentioning
confidence: 99%
“…Actin is ubiquitous in eukaryotes, but its existence has not been undisputably proven in Tetrahymena despite many attempts (1). Recently, the actin genes from Tetrahymena thermophila and Tetrahymena pyriformis were isolated, respectively, by Cupples and Pearlman (2) and by ourselves (3).…”
mentioning
confidence: 99%
“…The presence of LdACT in the construct was examined by restriction enzyme digestion and the nucleotide sequence was confirmed by DNA sequencing using the dideoxy chain termination method (25). 40 g of both the p6.5-LdACT construct and p6.5 control plasmids were transfected separately into 10 7 L. donovani promastigotes by electroporation (26). Transfected cells were further selected in the growth medium containing tunicamycin up to 20 g/ml and maintained in the same conditions.…”
Section: Plasmid Construction Transfection and Expressionmentioning
confidence: 99%